(3MQeI GdeScf ai GdbGfhf GdeUQi hGdfXGe GdSYhOi (B/ s - (3agO Hf fGja GdWQjSis; (3eGehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2003)
(3Cf MQeI GdeScf ef GdMbhb GdCSGSjI GdJj MXjJ HCgejI HGdZI ef GdTQjYI GdESdGejI hGdehGKjb hGdEJaGbjGJ GdOhdjI dPdc MGhdfG EdbGA GdVhA YdjgG ef GdfGMjI GdELQGFjI aj Xd GdbGfhf GdeUQj haj Xd GdfXGe aj GdeedcI GdYQHjI GdSYhOjI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2003s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B199-206s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGfhf GdeUQis; (3GdeScfs; (3GdfXGe GdSYhOis; (3JaJjT GdeScfs; (3BKGQ GdJaJjTs; (3VeGfGJ eQGbHI GdeMGOKGJ GdgGJajI s; (3GdJUfJs; (3VHW GdYbGQs; (3GdJTQjYs; (3TQhW GdOaY HGdHWdGfs; (3VHW GdeQGSdGJ hGdNWGHGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs